Mapping Power and Collaboration in Urban Data Governance: A Complex Network Analysis of Social Actors in Brazil - Cavalcanti, Isabella; Tramontano, Marcelo (Anais do Latin American Symposium on Digital Government (LASDiGov); 2026: Anais do XIV Latin American Symposium on Digital Government, 2026)
Urban data governance is increasingly shaped by sociotechnical infrastructures that may reproduce structural inequalities, particularly in Global South contexts. This paper examines how social actors are structured and interconnected in urban data governance in Brazil through the GHZ Network, combining Social Network Analysis (SNA) and critical data studies. Based on documentary research and relational sampling, we constructed a network of 35 core actors and 809 connected entities, modeling collaborations, funding relations, and data exchanges. Results reveal a sparse yet highly connected network, dependent on a small number of intermediary actors—primarily civil society organizations—while public sector actors exhibit low centrality. The analysis also highlights territorial concentration in Brazil’s South–Southeast and the influence of international funders, pointing to governance asymmetries. The study contributes a replicable framework for mapping sociotechnical networks and provides insights into how network structures relate to power and inequality in urban data governance.